2010
DOI: 10.4314/swj.v3i3.51813
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of dumpsite leachate on the qualities of surface Water and sediment of river eku, ona-ara local government, Oyo State, Nigeria.

Abstract: River Eku, a water body in Ona-Ara Local Government of Oyo State was studied to assess the impact of dumpsite leachate on the qualities of surface water and sediment of the river. The mean values for dissolved oxygen (DO) (2.3  1.1 mg/L), chemical oxygen demand (COD) (822  658 mg/L), PO4 3-(0.35  0.20 mg/L), SO4 2-(16.45  2.95 mg/L) were reported for the upstream region, while the downstream mean values for the same parameters gave 3.73  0.56 mg/L, 911.75  813.36 mg/L, 0.68  0.42 mg/L, and 26.18  4.46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
4
4
0
Order By: Relevance
“…Some fungi strains isolated include: Penicilum sp, Aspergillus niger; Curvularia sp; Alternaria sp; Fusarium sp; this is in concordance with the work of Nubi et al, (2008) who reported Geotrichum candidum, Tichosporon and Penicillum as fungi community found in effluents just as Penicillium sp was isolated from the studied samples in this research work.…”
Section: Discussionsupporting
confidence: 80%
“…Some fungi strains isolated include: Penicilum sp, Aspergillus niger; Curvularia sp; Alternaria sp; Fusarium sp; this is in concordance with the work of Nubi et al, (2008) who reported Geotrichum candidum, Tichosporon and Penicillum as fungi community found in effluents just as Penicillium sp was isolated from the studied samples in this research work.…”
Section: Discussionsupporting
confidence: 80%
“…Wastes are sources of environmental pollution through the introduction of toxic substances above their threshold limit into the environment. However, in Nigeria, most of the active dumpsites are now located within the city due to population influx and expansion [ 2 , 3 ]. Recent studies have shown that waste disposal on dumpsites introduces additional heavy metals into surrounding soil [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that waste disposal on dumpsites introduces additional heavy metals into surrounding soil [ 2 ]. Soil is a natural reservoir of metals whose concentration is associated with several factors such as parent material, pH and organic matter (OM) [ 3 ]. In the last few decades, metal contents in soils have risen to dangerous levels mainly due to human activities such as industrialization and urbanization [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…[26], in their study, explained that soils at refuse dumpsites contain different kinds and concentrations of HM depending on the age, contents and location of the dumpsite. Similarly, many studies have shown that continuous disposal of municipal wastes may increase the HM concentration in the soil and underground water [27][28][29][30]. Welders and other mechanics associated with the automobile industry also release a lot of Cd in the environment.…”
Section: Discussionmentioning
confidence: 99%